0131 The ontological shift – the influence an interprofessional full patient simulation session can have on a medical students' learning. (2nd November 2015) - Thomas, Libby; Gill, Elaine
Abstract : Background: Undergraduate full patient simulation (FPS) is commonplace. FPS course evaluations show that clinical knowledge and skills are improved. But what do the students really take away from the experience? Methodology: Final year medical, nursing and midwifery students participated in an interprofessional FPS course. A phenomenological approach 1 and analysis 2 explored 'meaning' and transfer of learning into their clinical practice. The ontological shift is one of the resulting themes. Outcomes: The students described a change in the way they observed and participated in their clinical placements post the FPS experience. Student GK explores these issues: GK Because I had a really good experience and I learnt from it, I went back to the ward, and I was remembering, actually, do you know what? Yes, I can see, that's why I was looking at the nurses, I was looking at the F1, and the nursing interaction as well. And we had a deteriorating patient, and the other F1s, the other student wasn't there. And I offered to help, obviously, and I saw how it worked. I saw how the nurses worked, and I thought it was really good. I guess you don't realise it until you've been put into that situation. Key changes described include: Observing the doctors role differently Observing the interaction between healthcare professionals Using other healthcare professionals as a learning resource Increased confidence to participate in clinical activities Conclusions: An ontological shift can be deemed to have occurred when the subject starts thinking about an 'entity' in a new way and categorises it differently. The students describe new ways (for them) of observing practice and behaviours in the clinical arena and re-conceptualise clinical problems, thereby seeing the clinical world in a new light – an ontological shift. References: Moustakas C. Phenomenological research methods . London: Sage Publications, 1994 Creswell, JW. Qualitative inquiry and research design; choosing among five approaches . London: Sage Publications, 2007